Republic of Estonia : Update to the Report on the Observance of Standards and Codes, 2002-Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents an update to the Report on the Observance of Standards and Codes (ROSC) for Banking Supervision, Data Module, Fiscal Transparency Module, Insurance Supervision, Payment Systems, Securities Supervision, and Transparency in Monetary and Financial Policies for the Republic of Estonia. Beginning from January 1, 2002, the unified Estonian Financial Supervision Authority is responsible for banking, insurance, and securities market supervision. Relevant provisions to the Credit Institutions Act (Article 84) were extended to managers of shareholders and to companies in which managers hold a qualifying interest.